Exosome‐delivered miR‐221/222 exacerbates tumor liver metastasis by targeting SPINT1 in colorectal cancer. Issue 9 (7th July 2021) - Tian, Fei; Wang, Peiyun; Lin, Dan; Dai, Jiajia; Liu, Qibing; Guan, Yu; Zhan, Yang; Yang, Yichen; Wang, Wenpeng; Wang, Jiefu; Liu, Jia; Zheng, Lei; et al.
Abstract: MicroRNAs (miRNAs) are involved in the progression of many cancers through largely unelucidated mechanisms. The results of our present study identified a gene cluster, miR‐221/222, that is constitutively upregulated in serum exosome samples of patients with colorectal carcinoma (CRC) with liver metastasis (LM); this upregulation predicts a poor overall survival rate. Using an in vitro cell coculture model, we demonstrated that CRC exosomes harboring miR‐221/222 activate liver hepatocyte growth factor (HGF) by suppressing SPINT1 expression. Importantly, miR‐221/222 plays a key role in forming a favorable premetastatic niche (PMN) that leads to the aggressive nature of CRC, which was further shown through in vivo studies. Overall, our results show that exosomal miR‐221/222 promotes CRC progression and may serve as a novel prognostic marker and therapeutic target for CRC with LM. Abstract : MiR‐221/222 is frequently upregulated in serum exosomal samples of patients with colorectal carcinoma (CRC) liver metastasis (LM). CRC exosome–delivered miR‐221/222 exerts a vital effect in promoting liver‐specific metastasis through remodeling the liver microenvironment. Tumor‐derived exosomal miR‐221/222‐3p can induce hepatic stromal cells to secrete HGF in the premetastatic niche (PMN).